1987
DOI: 10.1097/00132586-198710000-00054
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Discontinuation of Total Parenteral Nutrition

Abstract: The present study was undertaken to assess the impact of acute discontinuation (AD) of total parenteral nutrition (TPN) on serum glucose, insulin, and glucagon levels and on the generation of symptomatic hypoglycemia. Fifty studies were performed in 48 patients. In none of the 30 studies of 1 hour duration nor in the 20 studies of 8 hours duration was there a single episode of symptomatic hypoglycemia. One patient had a glucose below normal (60 mg/dl) during the first hour after AD. Glucose and insulin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A total of 86 adult patients from 4 studies who had their PN stopped abruptly with no taper down, showed transient decreases in BG, mainly within the first hour after stopping the PN, with no patients experiencing symptomatic hypoglycemia. One randomized, controlled trial crossover study of 12 patients receiving cyclic PN, comparing taper down and no taper down, showed no significant differences between taper and no taper in the mean BG, insulin, epinephrine, norepinephrine, glucagon, growth hormone, or cortisol levels when checked before taper or abrupt discontinuation and every 15 minutes for 1.5 hours after discontinuation of PN.…”
Section: Opportunities For Optimizing the Ehr In The Pn Workflowmentioning
confidence: 99%
“…A total of 86 adult patients from 4 studies who had their PN stopped abruptly with no taper down, showed transient decreases in BG, mainly within the first hour after stopping the PN, with no patients experiencing symptomatic hypoglycemia. One randomized, controlled trial crossover study of 12 patients receiving cyclic PN, comparing taper down and no taper down, showed no significant differences between taper and no taper in the mean BG, insulin, epinephrine, norepinephrine, glucagon, growth hormone, or cortisol levels when checked before taper or abrupt discontinuation and every 15 minutes for 1.5 hours after discontinuation of PN.…”
Section: Opportunities For Optimizing the Ehr In The Pn Workflowmentioning
confidence: 99%
“…Once a patient is taking at least 60% of caloric needs either by mouth or by EN, PN can be discontinued. Tapering the infusion is not required, as abrupt discontinuation has not been demonstrated to cause symptomatic hypoglycemia 47, 48…”
Section: Implementation Of Nutrition Care Planmentioning
confidence: 99%
“…64 Strategies for reducing this rebound hypoglycemia include gradual taper of PN infusion rate over 1-2 hours before discontinuation and establishing oral diet or enteral nutrition (EN) tolerance prior to PN discontinuation. 65,66 EFAD Essential fatty acids, or those that cannot be synthesized by the body, include linoleic acid (an ω-6 fatty acid) and α-linolenic acid (an ω-3 fatty acid). These are further converted in the body to arachidonic acid and eicosapentaenoic acid, both essential for second-messenger formation in the body.…”
Section: Hyperglycemiamentioning
confidence: 99%